RURAL REVITALIZATION THROUGH TOURISM: SPATIAL ANALYSIS OF NOHAKU ACCOMMODATION DISTRIBUTION AND PRICING IN YAMAGUCHI PREFECTURE, JAPAN - Wenting Zhou (GeoEco, 2025)
Research into the supply of tourism accommodations in rural areas is essential, given tourism's central role in rural revitalisation. Recent studies increasingly employ Geographical Information Systems (GIS) to analyse the distribution and determinants of rural accommodations. However, a significant gap remains in the literature addressing rural Japan specifically. This study investigates the spatial distribution and pricing dynamics of Nohaku accommodations in Yamaguchi Prefecture, Japan. A comprehensive database was compiled from multiple sources to document accommodations and their respective prices across Japanese prefectures. The analysis integrates spatial analysis and the Spatial Durbin Model (SDM) to assess spatial clustering and the determinants of accommodation pricing. Results reveal significant clustering of Nohaku accommodations around key tourism resources and identify regions with untapped tourism potential. Spatial econometric analysis shows that Nohaku accommodations command a price premium, and proximity to tourism resources positively affects pricing. The results offer a nuanced understanding of spatial patterns and pricing strategies, providing actionable insights for policymakers to optimise rural tourism development.